Pendekatan Restorative Justice dalam Penyebaran Berita Bohong (Hoaks) Terkait Covid-19 - I Ketut Arya Darmawan; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
The number of Hoax cases that occurred in the community has increased. Hoax is not only a problem in itself but has a broad impact on various events. Moreover the need for sanctions against those who spread hoax news. This study uses a normative legal research type. The data collection technique in this study was carried out by literature study. Sources of legal materials used are sources of primary legal materials and sources of secondary legal materials in the form of theories, literature, and scientific works. The results of this study indicate that the Restorative Justice approach can be applied to the perpetrators of spreading hoaxes related to Covid-19. The application of Restorative Justice is in accordance with the philosophy of the Indonesian nation, namely Pancasila, especially the 4th precept, which emphasizes deliberation. Sanctions for the perpetrators of spreading hoaxes related to Covid-19 are imprisonment and fines. To reduce the impact of hoaxes circulating on social media, it is better if people filter news so that people as social media users do not violate applicable regulations.